Integration of ARPA with Bridge Resource Management (BRM) to Enhance the Effectiveness of Collision Prevention in Merchant Vessels - Wiwik Handayani; Abdul Halik; Siti Mujanah (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Collision accidents at sea remain a serious threat to commercial shipping, particularly in high-traffic waters. Although navigation technologies such as ARPA (Automatic Radar Plotting Aid) can provide predictions on vessel positions, speed, and safe distances between ships, human error, miscommunication, and suboptimal use of the system still frequently occur in practice. This article examines the integration of ARPA with Bridge Resource Management (BRM) in the context of merchant vessels, as a strategy to strengthen collision prevention. The method employed is a comprehensive literature review, case study analysis, and the proposal of an integrative model. The findings indicate that the ARPA–BRM integration enhances situational awareness, bridge team coordination, collective decision-making, and proactive risk mitigation capabilities. It is recommended that vessel training (including ARPA & BRM simulators) and operational policies strengthen this synergy to ensure safer navigation.